Spatio-temporal patterns in arctic fox (Vulpes alopex) diets revealed by molecular analysis of scats from Northeast Greenland - Schmidt Niels Martin; Roslin Tomas; Hansen Lars Holst; Gilg Olivier; Lang Johannes; Sittler Benoit; Hansen Jannik; Bollache Loïc; Vesterinen Eero (Elsevier B.V., 2022)
The arctic fox (Vulpes lagopus) is endemic to the Arctic where it holds a central position in the trophic interactions. The diet of the species has previously been described as being highly flexible, but whether this flexibility is a constant trait through time, or merely reflects fast temporal changes in abundance among prey taxa, has so far been poorly resolved. Using molecular analyses of arctic fox scats from Northeast Greenland, we first examined the temporal dynamics of arctic fox diets during the short snow-free season, and then examined whether local food availability at different sites affected arctic fox dependence on lemmings. Arctic fox diets included most terrestrial vertebrate species found in the region, and exhibited substantial temporal changes, generally reflecting the dynamic changes in prey availability from late winter through autumn. This dietary flexibility was also reflected geographically, with arctic foxes consuming a variety of local prey (mainly waterfowl and lemmings) in summer. Moreover, the dietary response of arctic foxes to changes in lemming abundance depended on access to non-lemming prey. Based on these findings, we discuss whether varying degrees of lemming-dependency, combined with geographical differences in winter food availability, may explain previously published differences in arctic fox breeding patterns in high arctic Greenland.